ADJUSTMENT OF THE FEEDING LEVEL OF MEAT-TYPE COWS WITH DIFFERENT LIVE WEIGHT AND FATNESS - R. M. Mudarisov; I. N. Khakimov; V. G. Semenov; D. A. Baimukanov; A. T. Varakin; N. I. Kulmakova; L. A. Korosteleva; K. Zh. Iskhan; K. B. Apeev (Scientific Journal of Pedagogy and Economics, 2019)
For the first time, on the basis of comprehensive research, it was scientifically substantiated and experimentally proved the feasibility of changing the feeding level of cows of specialized meat-type breeds that have a different score of fatness when using the regression coefficient between fatness and live weight. For efficient production of high-quality beef, it is not enough to have specialized beef breeds with high genetic potential and high-quality feed. Of great importance is the management of technology for feeding, rational use of forage and animals. Currently, standards for feeding meat-type cows are recommended, calculated depending on their live weight. This is an insufficiently substantiated approach, as in a group, animals can have the same live weight, different fatness,and energy need.The rates of cow feeding should be adjusted not only taking into account their live weight, but also the fatness of animals. In this case, the formation of groups, depending on the fatness, becomes an obligatory technique in the technological chain of beef production that will save feed, since in the cost structure of beef a large proportion of the costs fall on feed (60% or more), as well as increase the profitability of the industry.